OBSERVATIONS ON THE SECONDARY SEXUAL CHARACTERS OF HIPPOLYSMATA ENSIROSTRIS KEMP - Sukumaran, K K (Indian Journal of Fisheries, 2011)
Hermaphrodites are seldom found among prawns. In Hippotysmata ensirostris Kemp, a commercially important shrimp of Maharashtra belonging to the family Hippolytidae hermaphroditism has been observed as a regular feature and this is the first record of its kind in this species. The prawn matures as male in the early part of it; life and later, changes its sex completely and functions as female during the remaining period. Subsequent changes in the secondary sex characters have been noticed in the sex change